Characteristics of body scrub from seaweed (Ulva lactuca) and turmeric rhizome (Curcuma longa) - Leku Putri Raihanna; Dini Surilayani; Ginanjar Pratama; Afifah Nurazizatul Hasanah (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Ulva lactuca is one of the green seaweeds that widely developed as a cosmetic preparation. U. lactuca has the potential to be used as seaweed salt and the residue of seaweed salt can be used as a body scrub preparation material. In addition, natural ingredients that can be used for cosmetic preparations are turmeric (Curcuma longa) rhizome. This study aimed to determine the optimum formulation and the best physical characteristics of seaweed (U. lactuca) and turmeric (C. longa) rhizomes. This study was experimental with four treatments and two replications, the concentration of the scrub preparation was 7% U. lactuca salt residue and 0.5%, 1% and 1.5% turmeric rhizome powder. The best body scrub preparation is the F3 treatment with a pH value, viscosity and spreadability that meets the requirements for cosmetic preparations, all treatments can moisturize the skin and do not cause irritation to the skin, has an M/A emulsion type, a body scrub preparation that is stable, has the appearance, texture, panelists preferred color and aroma. All treatments showed that formulations with the addition of gram residues of U. lactuca and turmeric rhizome could affect the characteristics of the resulting scrub preparations.